2009
DOI: 10.1007/s10151-009-0467-5
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic lymph node ratio as an independent prognostic variable in colorectal cancer: study of 113 patients

Abstract: The results showed that the LNR can be considered an independent prognostic variable in overall survival of patients with colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…Park et al (2011) in a study on 186 stage III colorectal cancer patients had selected cutoff point of LNR as 0.07 Several studies (Peschaud et al, 2008;Kim et al, 2009;Priolli et al, 2009;Dekker et al, 2010;Rosenberg et al, 2010;Thomas et al, 2012) had chosen different cutoff points by different parameters such as quartiles, median value and arbitrary values. The cutoff points for LNR were proposed in many studies but the optimal level need to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al (2011) in a study on 186 stage III colorectal cancer patients had selected cutoff point of LNR as 0.07 Several studies (Peschaud et al, 2008;Kim et al, 2009;Priolli et al, 2009;Dekker et al, 2010;Rosenberg et al, 2010;Thomas et al, 2012) had chosen different cutoff points by different parameters such as quartiles, median value and arbitrary values. The cutoff points for LNR were proposed in many studies but the optimal level need to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, only 3 studies have studied the LNR in 2 groups. These groups were based on the quartiles 18,19 or the mean LNR 20 and not on the correlation between LNR and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Ceelen et al [42], in a systematic review of the prognostic value of the LNR in stage III colorectal cancer, stated that it is a stronger prognostic factor than the number of LN for both colon and rectal cancer patients. All identified studies about rectal cancer [43][44][45][46][47][48][49][50] showed that the LNR is an independent predictor of overall survival and disease-free survival. In particular, Rosenberg et al [46] in 1,263 rectal cancer patients over a 25-year time period and Peschaud et al [47] in 307 patients with high, mid, or low rectal cancer reported LNR as an independent prognostic factor, even when fewer than 12 LN were examined.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Rosenberg et al [46] in 1,263 rectal cancer patients over a 25-year time period and Peschaud et al [47] in 307 patients with high, mid, or low rectal cancer reported LNR as an independent prognostic factor, even when fewer than 12 LN were examined. Nevertheless, several limitations apply to the interpretation of the results of these studies: most did not separately analyze intra-and extraperitoneal rectal cancer patients [43,46,47], and some included only upper rectal cancer patients [50], had a median follow-up period of less than 5 years [45,[47][48][49][50], did not report data regarding the surgical technique used [43,49], or included patients operated on before the introduction of TME [43,46]. Moreover, different cutoff values for LNR were proposed based mainly on quartiles classification rather than a single value.…”
Section: Discussionmentioning
confidence: 99%